2021
DOI: 10.1016/j.aninu.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of yeast on rumen fermentation, growth performance and quality of products in ruminants: A review

Abstract: This review aims to give an overview of the efficacy of yeast supplementation on growth performance, rumen pH, rumen microbiota, and their relationship to meat and milk quality in ruminants. The practice of feeding high grain diets to ruminants in an effort to increase growth rate and weight gain usually results in excess deposition of saturated fatty acids in animal products and increased incidence of rumen acidosis. The supplementation of yeast at the right dose and viability level could counteract the acido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 111 publications
(197 reference statements)
4
65
2
3
Order By: Relevance
“…In addition to its potential function in oxygen scavenging [ 71 ], S. cerevisiae has been proved to promote the growth of cellulolytic microbes (e.g., F. succinogenes , R. albus ), LUB (e.g., S. ruminantium ), and amylolytic bacteria (e.g., Ruminobacter , Bifidobacterium ), potentially leading to higher VFA concentration in the rumen after the supplementation [ 72 , 73 ]. This promotion effect may be explained by the fact that S. cerevisiae may provide growth factors, such as organic acids, vitamins, or amino acids, to stimulate ruminal bacterial populations [ 74 ]. The supplementing S. cerevisiae could also lead to improved microbial nitrogen metabolism thus increasing microbial protein flow to the intestine and reducing N loss [ 75 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its potential function in oxygen scavenging [ 71 ], S. cerevisiae has been proved to promote the growth of cellulolytic microbes (e.g., F. succinogenes , R. albus ), LUB (e.g., S. ruminantium ), and amylolytic bacteria (e.g., Ruminobacter , Bifidobacterium ), potentially leading to higher VFA concentration in the rumen after the supplementation [ 72 , 73 ]. This promotion effect may be explained by the fact that S. cerevisiae may provide growth factors, such as organic acids, vitamins, or amino acids, to stimulate ruminal bacterial populations [ 74 ]. The supplementing S. cerevisiae could also lead to improved microbial nitrogen metabolism thus increasing microbial protein flow to the intestine and reducing N loss [ 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…The supplementing S. cerevisiae could also lead to improved microbial nitrogen metabolism thus increasing microbial protein flow to the intestine and reducing N loss [ 75 ]. Alternatively, the competition with LAB for available sugar can contribute to the potential of SARA alleviation [ 74 ]. However, the persistence and viability of live yeast cells are reported to be low in the rumen since certain strains cannot colonize the rumen for a long period of time [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, YC is supplemented to the diet of dairy cows because of its role in the stabilisation of rumen pH ( 6 , 7 ). YC may have a similar effect on the rumen pH of sheep when fed high-grain diets ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…These meats are rich in polyunsaturated fatty acids (PUFA), and which present relatively simple production processes. Our previous study indicated that the nature of the diet is an essential factor that influences the composition of intramuscular fatty acids (FA) in lambs, whose family FAs n3 are more representative in those fed on steppe plants (Rabah et al, 2019), other studies also confirm the influence of diet on FA (Díaz et al, 2005;Ružić-Muslić, 2012), however, other intrinsic and extrinsic factors may influence and be responsible for the difference in FA such as sex, age, type of breeding, transport to the slaughterhouse, conservation of meat (De Smet et al, 2003 ;Amin and Mao, 2020). Currently, many ruminant breeders tend to modify their feeding practices by reducing the diet based on concentrate, and are now moving more and more to pasture grass which confers little fat in the ruminant carcass compared to that based on concentrate (Daley et al, 2010).…”
Section: Introductionmentioning
confidence: 96%